SKOLOMBO AND THEIR CONTINUED EXISTENCE: REVISITING LOST HUMANISM AND PARENTIFICATION IMPULSE - OKAM, CHINYERE L. (Society Register, 2020)
This paper examines the Skolombo-street children of Calabar. It also investigates the reason for their continued existence, the derivatives in form of social and economic insecurity, inequality and other monstrosities visible in their presence. It questions the oblivious role of the institutions responsible for the care of the child, and parentification impulse as well as the lost humanism which existed in high premium in traditional African society resisted and reflected by text and language. The study is anchored upon Theo Van Leeuwen’s perspective on Critical Discourse Analysis which primarily studies the way social-power abuse and inequality are enacted, reproduced, legitimized, and resisted by text and talk in the social and political context. The study is a qualitative research conducted with the eclectic research methodologies such as biography, Participant Observation and Conversation. Among other findings, this study reveals that the Cross river state government has not provided enough fair ground to fully tackle the social and economic needs of the street child, that the desired comfort has not been provided for the girl child and that they have not been able to fully integrate the Skolombo into the echelon of the privileged. Conclusively, this has created spaces for youth delinquency, thievery, moral laxity and decadence. In the light of the findings, it is recommended that the government needs to put alternative and effective measures to play with the aim to curbing the menace of Skolombo and the street child culture. There ought to be an implementation of the child right boy and girl child. Stringent punishment should be meted on parents, religious leadact in the global space in order to reduce the molestation and marginalization of the ers and guardians who subject children to unnecessary molestation. Religious leaders and parents should be sensitized about the need to integrate their children within the family, intervention should be made compulsory.